Sinapic Acid Ameliorates the Progression of Streptozotocin (STZ)-Induced Diabetic Nephropathy in Rats via NRF2/HO-1 Mediated Pathways - Alaofi, Ahmed L. (Frontiers in Pharmacology, 2020)
Diabetic nephropathy (DN) is a major cause of end-stage kidney failure. The present study examines the amelioration of the renal protection of sinapic acid (SA) in streptozotocin (STZ)-induced diabetic nephropathy and the associated mechanisms. Rats were randomly assigned into four groups: Normal control (NC), STZ, STZ + SA 20 mg/kg bw, and STZ + SA 40 mg/kg bw. After eight weeks, the fasting blood glucose (FBG), ratio of kidney weight to body weight (renal index), 24 h urine protein, blood urea nitrogen (BUN), serum creatinine (SCr), reduced glutathione peroxidase (GPx), superoxide dismutase (SOD), lipid peroxidation (LPO), inflammatory marker MPO, tumor necrosis factor α (TNFα), interleukin (IL)-6, as well as lipid profile total cholesterol (TC), total triglycerides (TG), very low density lipoprotein (VLDL), low density lipoprotein (LDL), and high density lipoprotein (HDL) levels were assesed. The histomorphology and ultrastructure of the kidneys were also assessed. In addition, protein expression levels of transforming growth factor-β1 (TGF-β1), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), IκBα protein (IkBα), anti-apoptotic protein BCl2 , nuclear factor kappa B (NF-kB), and Bax were examined. We found that SA 20 mg/kg and 40 mg/kg pretreatment significantly and dose-dependently upregulated the expression of Nrf2, HO-1, IKBα, and Bcl-2 but downregulated the expression of NF-κB, suggesting that the protective mechanism of SA is due to its antioxidant and inflammatory activity; SA prevents the release of pro-inflammatory cytokines and inflammatory markers (TNFα IL-6 and MPO), upregulates antioxidant defence enzymes, and reduces lipid peroxidation, as well as nitric oxide, and anti-apoptotic activity, which may be influenced by the regulation of MPO, TNF-α, IL-6, Bcl-2, NF-kB, and BaX via the Nrf2/HO-1 signaling pathway in STZ induced DN. Thus, our results suggest that SA ameliorates the progression of STZ-induced diabetic nephropathy in rats via NRF2/HO-1 mediated pathways. Further comprehensive studies are required to better understand the underlying mechanisms.